Perceived stress during resuscitation: a scale development study - Asuman Şener; Tuğba Çınarlı; Dilan Köse (BMC Nursing)
Abstract Background Considering that resuscitation is a very stressful situation, it is very important to use a tool to determine perceived stress during resuscitation. There is no valid and reliable measurement tool to examine perceived stress during resuscitation in Türkiye. The objective of this study was to develop the Perceived Stress During Resuscitation Scale for healthcare professionals who have an important role in resuscitation and to validate its psychometric properties among emergency nurses. Methods Based on the literature review and expert review, a four-point Likert-type 52-item scale was prepared. Item analyses, exploratory factor analysis, confirmatory factor analysis, concurrent and predictive validity and reliability studies were conducted to investigate the psychometric properties of the scale. Data were obtained from 348 emergency nurses registered in 11 hospitals in Turkey between August 2023 and October 2023. Results After confirmatory factor analysis, the scale consisting of 7 sub-dimensions (inadequate working conditions, ethical difficulties, insufficient authority, failed resuscitation effort, difficulties caused by patient relatives, emotional pressure caused by patient/patient relatives, unexpected situations) was finalized with 27 items. The Cronbach’s α reliability coefficient of the scale was 0.891 and the values for the sub-dimensions ranged between 0.672 and 0.863. Conclusions The Perceived Stress During Resuscitation Scale is a valid and reliable measurement instrument for emergency nurses. The scale will enable the development of appropriate strategies by investigating the factors affecting perceived stress in nurses during resuscitation. Clinical trial number Not applicable.